2008
DOI: 10.1016/j.abb.2008.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Functions of RANKL/RANK/OPG in bone modeling and remodeling

Abstract: The discovery of the RANKL/RANK/OPG system in the mid 1990s for the regulation of bone resorption has led to major advances in our understanding of how bone modeling and remodeling are regulated. It had been known for many years before this discovery that osteoblastic stromal cells regulated osteoclast formation, but it had not been anticipated that they would do this through expression of members of the TNF superfamily: receptor activator of NF-κB ligand (RANKL) and osteoprotegerin (OPG), or that these cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
1,104
4
50

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,479 publications
(1,177 citation statements)
references
References 105 publications
19
1,104
4
50
Order By: Relevance
“…21,41 Importantly, this truncated protein contained an intact Runt DNA binding domain and domains interacting with Runx2 partner proteins, such as CBF and Smad3/4. 21,42 Using SM22aCre to remove Runx2 in vascular SMCs of ApoE À/À mice with this model, the authors found significantly reduced SMC elaboration of RANKL, a tumour necrosis factor family member important for monocyte infiltration and differentiation of mineral-resorbing osteoclasts, 43,44 along with a near complete blockage of monocyte/macrophage recruitment and atherosclerosis. 21 AIC was also completely blocked likely due to the inhibition of oxidative stress-dependent osteogenic differentiation and osteoblast-osteoclast crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…21,41 Importantly, this truncated protein contained an intact Runt DNA binding domain and domains interacting with Runx2 partner proteins, such as CBF and Smad3/4. 21,42 Using SM22aCre to remove Runx2 in vascular SMCs of ApoE À/À mice with this model, the authors found significantly reduced SMC elaboration of RANKL, a tumour necrosis factor family member important for monocyte infiltration and differentiation of mineral-resorbing osteoclasts, 43,44 along with a near complete blockage of monocyte/macrophage recruitment and atherosclerosis. 21 AIC was also completely blocked likely due to the inhibition of oxidative stress-dependent osteogenic differentiation and osteoblast-osteoclast crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the balance between OPG and RANKL regulates bone resorption and formation [5][6][7]. Imbalance of the RANKL/OPG system have been implicated in the pathogenesis of various primary and secondary bone malignancies [8].…”
Section: Introductionmentioning
confidence: 99%
“…RANKL, produced by osteoblasts, stimulates osteoclast differentiation through its cognate receptor RANK on the surface of osteoblasts. Therefore the RANKL-RANK system promotes the maturation of osteoclasts [4,5]. Osteoblasts also regulate the growth of osteoclasts by secreting OPG, a decoy receptor for RANKL and therefore a competitor of RANK, to restrain the activity of the RANKL-RANK system [4].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the RANKL-RANK system promotes the maturation of osteoclasts [4,5]. Osteoblasts also regulate the growth of osteoclasts by secreting OPG, a decoy receptor for RANKL and therefore a competitor of RANK, to restrain the activity of the RANKL-RANK system [4]. Thus, the ratio of RANKL to OPG dictate the activity of osteoclasts, the resorption of bone [1,24].…”
Section: Discussionmentioning
confidence: 99%